1998
DOI: 10.1002/(sici)1096-9071(199807)55:3<234::aid-jmv9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of respiratory syncytial virus in São Paulo State, Brazil

Abstract: Transmission of respiratory syncytial virus is thought to be highly seasonal based on reported clinical cases, although transmission resulting in mild disease in all age groups has been little studied. This has been investigated in a seroepidemiological survey using sera from São Paulo, Brazil. Seroprevalence was found to increase rapidly with age, reaching over 90% by three years of age. This is typical of viral infections, which produce life-long immunity following primary infection. One-hundred percent sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
45
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 21 publications
12
45
1
1
Order By: Relevance
“…The decrease in RSV-specific antibodies detected in infants <1 month to 6 months of age is consistent with the loss of maternal antibodies, as reported previously (5,18). In the present study, examination of sera from RSV-infected children revealed that the total IgG levels were higher than IgG1 levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in RSV-specific antibodies detected in infants <1 month to 6 months of age is consistent with the loss of maternal antibodies, as reported previously (5,18). In the present study, examination of sera from RSV-infected children revealed that the total IgG levels were higher than IgG1 levels.…”
Section: Discussionsupporting
confidence: 93%
“…The components of the immune response to RSV, which lead to protection or pathology, are not well understood, and this has hindered vaccine development (1,2). There is a considerable amount of data about the humoral response to human RSV infection (3)(4)(5), but limited information about the cellular immune response (6)(7)(8). Studies on humans and animals have demonstrated that antibodies are important contributors to protective immunity (9)(10)(11)(12) and that cellular immunity is important for clearing the infection (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous seroprevalence studies have shown that anti-RSV maternal antibodies remain in the infants' blood during this specific period of their lives, gradually decreasing until the sixth to seventh month of life. 8 An evaluation of antibodies during the convalescence phase was not performed in this study. This approach would certainly provide relevant information with regards to the infants' response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, to provide adequate protection against RSV-LTRI with the prophylactic use of immunoglobulins (RSVIg) or monoclonal antibodies in infants. [8][9][10][11] A reasonable explanation would be the lack of specificity of the maternal antibodies to the RSV genotype (subtype) infecting the infant, due to the known fact that circulating genotypes of RSV in a current season are substituted for others a few years later; therefore, the serum maternal antibodies at the time of infection would not correspond to the current infecting genotype, but rather to genotypes from previous years. 12,13 In order to test this hypothesis, the authors identified the type/genotype of the RSV detected in infants with LRTI, and evaluated the presence and amount of serum subtype-specific antibodies for the RSV genotype responsible for the infection.…”
Section: Introductionmentioning
confidence: 99%
“…As a result MAb are short lived and following birth, concentrations of IgG in the newborn decay exponentially with a typical half life of around 35-40 days [4]. Many seroepidemiological surveys have shown that most infants become seronegative within 6-9 months of age (see the work by Cox et al [5] and Hacimustafaoglu et al [2] for hRSV, Williams et al [6] for measles and Nicoara et al [4] for measles, mumps and rubella (MMR)).…”
Section: Introductionmentioning
confidence: 99%